Effective 137Cs+ and 90Sr2+ immobilisation from groundwater by inorganic polymer resin Clevasol® embedded within a macroporous cryogel host matrix. (November 2022) - Chaplin, J.D.; Berillo, D.; Purkis, J.M.; Byrne, M.L.; Tribolet, A.D.C.C.M.; Warwick, P.E.; Cundy, A.B.
Abstract: The conservative fission products 137 Cs and 90 Sr are of concern when present in groundwater, as they present a radiological hazard to organisms and can be transported long distances from their source. To provide an interceptive permeable reactive barrier (PRB) solution which accommodates the throughflow of groundwater whilst removing 137 Cs + and 90 Sr 2+, we report the synthesis of a novel composite cryogel which performs as a permeable hierarchical sorbent. This material incorporates the ion-exchanger Clevasol® into a PVA-based cryogel host matrix with interconnected macropores, producing a composite cryogel (Clevasol®-PVACC). Clevasol®-PVACC enables the in-situ deployment of an ion-exchanger with rapid uptake kinetics for 137 Cs + and 90 Sr 2+, inside of a robust and permeable scaffold with green chemistry. Clevasol®-PVACC has a facile, one-pot and scalable synthesis, and can possibly also be used at other stages of the nuclear fuel cycle, such as radioactive liquor treatment. Critically, the incorporated Clevasol® resin is vitrifiable, which is optimal for long-term storage and geological disposal if high activities are adhered onto the resin. The effective partition coefficients (kd ) and effective Langmuir uptake capacities (qmax ) of the Clevasol® resin in Sellafield groundwater simulant are respectively 10 5  mL/g and 298 mg/g for Cs +, and >10 4  mL/g and 128 mg/g for Sr 2+ . Graphical abstract: Image 1 Highlights: Clevasol® demonstrates excellent kd for Cs + and Sr 2+ from groundwater Novel Clevasol®-embedded cryogel composite synthesised Cryogel matrix accommodates throughflow of water The composite material suits batch and through-flow treatment modes Green chemistry and Clevasol® is vitrifiable for radioactive waste disposal